THE INFLUENCE OF TECHNOLOGY USE ABILITY AND ONLINE LEARNING POLICY DURING THE CORONA PANDEMIC ON THE QUALITY OF EDUCATION AT MTs. AL HUDA PANGKALAN SUSU - Sri Anitawati (Journal of Educational Science Learning and Research, 2024)
At MTs Al Huda Pangkalan Susu, teachers' technological abilities during the pandemic have had a big impact on the quality of education. This is because learning during the pandemic was carried out online. The aim of this research is to look at how the quality of education during Covid has been implemented as the government's online learning policy has been implemented. The research was conducted at MTs Al Huda Pangkalan Susu from January - March 2024. This research is quantitative research, the population and sample size are the same, namely 12 people, using the Totally Sampling method. There is a positive and significant influence of interpersonal communication on the quality of learning. amounting to 29.3%. There is a positive influence and use of technology on teacher performance of 71.0%. There is a positive and significant influence on the quality of learning of 70.9%.